Analisis Kebijakan Dividen dan Ukuran Perusahaan Terhadap Keputusan Investasi pada Perusahaan LQ45 - Dika Fajri Ilham; Agus Munandar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Research This research is to understand the correlation of an independent variable with the dependent variable. Research instruments to test the presence or absence of the influence of independent variables, namely dividend policy and company size on investment decisions, on investment decisions. Companies that engaged in LQ 45 companies listed on the Indonesia Stock Exchange with quantitative research using secondary data from 2020 to 2020. Quantitative research using secondary data from 2020 to 2023 with a total of 22 companies. to 2023 with a total of 22 companies for 4 years so that the total population taken was 88 companies with 4 years of consistent dividend distribution. companies by distributing dividends 4 years consistently. How to take samples in this study required purposive sampling method, in order to select the types of companies listed on the IDX. select the types of companies listed on the IDX. The results of the study simultaneously simultaneous and partial results show that only dividend policy and company size have an influence on investment decisions. size have an influence on investment decisions.